Jalur Sutra Kesehatan: Upaya China Mencapai Kepentingan Geopolitik Melalui Diplomasi Vaksin - Agape, Gideon Candra (Jurnal Transformasi Global, 2021)
In early April 2021, China had contributed a vital role in the Covid-19 vaccine export. With the national pharmaceutical company Sinovac and Sinopharm China capable of producing over 250 million doses of vaccine, 118 million have been successfully exported to 49 countries according to Airfinity. The world distribution of the covid-19 vaccine has been deemed a failure by the WHO, from 448 million global doses only 0.1 percent of the vaccine were administered to low-income countries, and rich countries which hold 16 percent of the world's population receiving nearly half a global dose. China is able to answer the world's frustration with the western nationalism vaccine issue, as the EU and USA failed to help low-income countries to provide vaccine access. The nationalism vaccine discourages equality, as 200 million doses of vaccine produced by the United States government had approximately exported only about 4 million doses to other countries. This paper will answer how China gains global geopolitics through vaccine diplomacy? What is the role of diplomacy in promoting China's influence? Currently China focuses on expanding its influence over Asia and South America through vaccine diplomacy, under the BRI initiative this policy is then called the Health Silk Road. Keywords: Health Silk Road, Vaccine Diplomacy, Sinovac, Sinopharm